Il Cilento ‘fuori di sé’. Crisi e conflitti psicologici, sociali e culturali in un’emigrazione dal Sud Italia verso altri continenti (fine ‘800-‘900) - Domenico Ienna (EtnoAntropologia)
This anthropological research - connected to individual/collective criticalities and conflicts which interested the migratory movement from Cilento (Salerno) towards other continents (end '800-'900) - is planning to investigate the umpteenth challenge to which was called a southern culture which was, in the course of the centuries, on the fringe of society, also exhausted from serious difficulties. The contribution makes use of the analysis of many letters, sent from migrants to Americas and Australia to relatives and friends of native villages, to act as an intermediary between country frustrations and suffered/inebriating transoceanic "disorientations".